Molecular interactions and redox effects of carvacrol and thymol on myofibrillar proteins using a non-destructive and solvent-free methodological approach. (April 2018) - Lahmar, Aida; Akcan, Tolga; Chekir-Ghedira, Leila; Estévez, Mario
Abstract: The present study provides molecular insight into the effect of thymol and carvacrol on the oxidative damage caused to myofibrillar proteins by a hydroxyl-radical generating system (HRGS). An innovative model system was designed, in which gels, prepared with increasing levels of myofibrillar proteins, were oxidized by a HRGS (Fe 3+ /H2 O2, 60 °C and 7 days) in the presence of lipids. The molecular affinity between myofibrillar proteins and both terpenes, as well as their effect on the oxidative stability of the gel systems, were studied using a non-destructive and solvent-free procedure based on fluorescence spectroscopy. Carvacrol displayed more affinity than thymol for establishing chemical interactions with protein residues. Both terpenes exhibited a significant antioxidant potential against the generation of lipid-derived volatile carbonyls and against the formation of protein crosslinking. This procedure may be applied to meat products to assess the effectiveness of a given antioxidant additive without size reduction or sample processing. Graphical abstract: Unlabelled Image Highlights: Fluorescence spectroscopy was applied to study molecular interactions and binding affinities. Carvacrol displayed more binding affinity to myofibrillar proteins than thymol. Carvacrol and thymol protected proteins against a hydroxyl radical-mediated oxidation.